On a New Class of Vector Variational Control Problems. (26th October 2018) - Treanţă, Savin
Abstract: In this paper, we introduce geodesic (strongly) b -V-KT-pseudoinvex multidimensional control problems. This new class of multiobjective variational control problems, involving multiple integral cost functionals, is described such that every geodesic Kuhn–Tucker point is geodesic efficient solution. In addition, to illustrate the effectiveness of our main result, the paper is completed with an application.